Концепт "материнство" у східнослов’янських та арабських пареміях - Zavhorodnya, D. O.; Завгородня, Дар'я Олександрівна (Запорізький національний університет, 2018)
Стаття присвячена аналізу реалізації концепту “материнство” у східнослов’янських та арабських фольклорних пареміях, прислів’ях передусім. Визначено смислове наповнення вказаного концепту, зумовлене ціннісними орієнтаціями, закріпленими в культурі. Доведено подібність бачення постаті та ролі матері в родині та соціумі представниками зазначених культур. The aim of this research article is to compare concept “motherhood” in East Slavic and Arabic сulture as exemplified by paramiology of studied ethnoses. Concept is universal term for many scientific directions and is especially relevant in humanities (author cоmpares “concept” and “notion” as related terms). Formation of the conceptual system in the minds - the most important component of the process of inculturation. Interesting aspect is a comparison of concepts сontent in unrelated cultures, which makes it possible to study the specific national peculiarities of culture, as well as the peculiarities caused by the universality of universal human spiritual experience. The author considers lingvocultural approach to the study of concepts, рarticular attention is focuses on the national and value components of this phenomenon. In theoretical part is proved that concept includes mental, ethno-specifical and axiological layer. It has dynamic, mobile character and presents a micromodel of culture. In the practical part of the work the content of the concept of motherhood (lexical and conceptual levels) are analyzed, social and cultural-historical context are determined (definition of “motherhood”, traditional ideas about the role of the mother in the family and society, relation with ancient mythological beliefs). It’s proved that in East Slavic and Arab cultures a social status of the mother is high (the relationship between a mother and a child becomes a model for many social attitudes). The consequence is the idealization of women in the status of the “mother”. In the practical part the high assessment of the concept in the hierarchy of values of East Slavic and Arab cultures is shown. Absence of clearly defined negative assessments is emphasized (on the basis of the analysis of practical material). The following meanings (which form the content of the concept) are defined: the uniqueness of the mother's role, the indispensability of her personality, the need for respect, the meaning of finding solace, responsibility of child-rearing (and, as a consequence, inheritance), connection with the emotional sphere of life. The coincidence in the understanding of motherhood and the role of mother is due to the long standing functioning of the universal “mother”.
Concept "motherhood" in east slavic and arabic proverbs
Keywords: паремія; прислів’я; концепт; концептуальне поле; культурний компонент; ціннісний компонент; paremia; proverb; concept; conceptual field; cultural component; value component